Studi Penentuan Percepatan (Acceleration) Tanah Daerah Ampana, Balikpapapan, Bone, Bulukumba, Bau-Bau Akibat Gempabumi Donggala 28 September 2018 - Ansyah, Habri; Djayus, Djayus; Supriyanto, Supriyanto (GEOSAINS KUTAI BASIN, 2021)
Ground acceleration that was caused by an earthquake can cause damage both physical and material. The research aims to determine the value of ground acceleration and the effects caused by earthquake. The data used was secondary earthquake data occurred at Donggala on September 28 th, 2018 at 17:02:45 WIB, with the observation area Ampana (central Sulawesi), Bau-Bau (South East Sulawesi), Bulukumba (South Sulawesi), Bone (South Sulawesi), and Balikpapan (Balikpapan). Research data including epicenter coordinates data, coordinates of observation area and the depth of earthquake. From this data are further calculated epicenter distance and hypocenter distance. Ground acceleration value was analyzed by using the method M. V Mickey, Esteva, Mc. Guirre RK, Donovan, Oliviera and Guttenberg then connected with MMI scale. The results showed thatthe ground acceleration value of Ampana, Balikpapan and Bone was between 0.0004 g – 0.0730 g with damage effects I-V according to MMI scale. For Bulukumba and Bau-Bau was between 0.0003 g– 0.0220 g with damage effects I-IV according to MMI Scale.